Rotation Alleviated the Continuous Cropping Obstacle of Peanut (Arachis hypogaea L.) Cultivation and Optimized the Endophytic Bacterial Communities in Peanut Pods - Miao Liu; Pu Shen; Qi Wu; Haiyan Liang; Dianxu Chen; Liyu Yang (Plants)
Peanut (Arachis hypogaea L.) continuous cropping reduces yield and quality, but the effects of specific rotation methods on yield and endophytic bacterial colonization remain unclear. Based on five years of continuous cropping trial data, three different cropping systems (WF, annual summer peanut and winter fallow; GM, annual summer peanut and winter ryegrass; CR, summer peanut rotated with summer maize and winter wheat) were employed in this study to systematically analyze and evaluate the effectiveness of crop rotation in mitigating peanut continuous cropping obstacles and its underlying mechanisms. The results showed that CR increased pod yield by 33% and kernel nitrogen content by 6.8% compared to WF, while GM had a marginal effect (1.4% nitrogen increase). Microbial analysis (LEfSe/LDA) revealed that CR enriched beneficial bacteria (e.g., Actinobacteria, Corynebacteriales) in pods while suppressing potential pathogens (e.g., Gammaproteobacteria, Burkholderiales). These findings demonstrate that strategic crop rotation, particularly CR, mitigates continuous cropping obstacles by enhancing yield, improving kernel quality, and promoting beneficial endophytic bacterial communities. Our findings highlight the complexity of crop rotation system functioning and how interactions between cropping patterns and endophytic microbiota affect peanut yield and kernel quality.